Print Media and Electoral Process in Nigeria - Gift Ntiwunka; Nwaodike Chibuzor Ayodele; Adewale K. Kupoluyi (Department of Government Affairs and Administration, Universitas Muhammadiyah Yogyakarta, 2020)
Elections in many developing countries such as Nigeria remain complex and cannot be handled solely by the government, as a vibrant print media is part of this exercise. Unfortunately, the Nigerian electoral process cannot be said to enjoy free, fair, and credible elections. Research design for the study was descriptive research, which combined both qualitative and quantitative methods. The sample was divided into two categories of a total of eight hundred and twenty (820) questionnaire respondents and sixteen (16) key respondents and interviewees from the Federal Capital Territory (FCT), Abuja and Lagos State, being the hub of media establishments and highly cosmopolitan locations in Nigeria. The study used survey, interview, and observation methods of data collection. Quantitative analysis was done using responses elicited from structured questionnaires. Content analysis of qualitative data was carried out on the selected 10 print media publications based on national spread. Findings showed that the print media contributed to creating better perception of the nation’s electoral process by international observers (Mean = 3.9497, St.D = 2.20417), the print media embarked upon improper reportage, selective coverage and failed to report actual happenings during elections because of undue influence by politicians and proprietors media establishments, thereby misinforming the people. The study concluded that the print media is important for smooth electoral process during the period of the study (1999-2019), despite challenges such as inadequate funding, and non-adherence to professional ethics by some print media journalists. The paper recommends that the print media should be protected from undue influence by politicians and proprietors, to strengthen the electoral process in Nigeria.